Modern languages and learning strategies : in theory and practice - Grenfell, Michael, 1953- (Routledge, 1999)
Every secondary school pupil studies modern foreign languages as part of the curriculum, and some do so with considerably more success than others. This book looks firstly at the ways in which languages can be taught, and secondly at case studies that highlight the practical methods that will help teachers get the best results. The case studies included show that the best learners are those who have developed learning strategies that help them succeed. These learning strategies are examined through practical examples carried out in classrooms, and advice is given about ways in which te.